Compliant immune response of silk-based biomaterials broadens application in wound treatment - Tian, Zhiqiang; Chen, Hong; Zhao, Ping (Frontiers in Pharmacology, 2025)
The unique properties of sericin and silk fibroin (SF) favor their widespread application in biopharmaceuticals, particularly in wound treatment and bone repair. The immune response directly influences wound healing cycle, and the extensive immunomodulatory functions of silk-based nanoparticles and hydrogels have attracted wide attention. However, different silk-processing methods may trigger intense immune system resistance after implantation into the body. In this review, we elaborate on the inflammation and immune responses caused by the implantation of sericin and SF and also explore their anti-inflammatory properties and immune regulatory functions. More importantly, we describe the latest research progress in enhancing the immunotherapeutic and anti-inflammatory effects of composite materials prepared from silk from a mechanistic perspective. This review will provide a useful reference for using the correct processes to exploit silk-based biomaterials in different wound treatments.